The challenge of participatory projects for physical activity promotion: What to scale and how to scale? - Raluca Sommer; Maike Till; Lisa Boyer; Philipp Weber; Alexandra Sauter; Susanne Ferschl; Anne Herrmann-Johns; Karim Abu-Omar; Klaus Pfeifer; Peter Gelius (PLoS ONE)
Background Scaling up participatory physical activity innovations is complex. Evidence on their nature and how they become embedded in health systems and policies is limited. This paper draws on four participatory research projects promoting physical activity among various populations and settings in Germany to explore their unique participatory innovations and strategies to scale-up. Methods Document analysis and focus group interviews (n = 15) were used for a retrospective case study analysis based on the WHO-ExpandNet framework. 19 scientists of the project teams under study were approached and recruited by the authors during their collaborative work within the Capital4Health consortium. We performed a deductive content analysis to identify the innovation(s) scaled up, the implementers responsible for the process, and the context in which it took place. Results The strategies employed differed depending on the intended scale-up direction: for the transfer to other sites (horizontal scale-up), projects usually scaled a participatory method; when working towards institutionalization at the systems level (vertical scale-up), they tended to scale specific actions for physical activity promotion, particularly those shown to be successful in the pilot phase of the projects. Overall, scale-up followed a strategic plan, but was continuously adjusted to setting-specific challenges and emerging opportunities. Discussion Scaling participatory methods for physical activity promotion may require significant resources. Previously developed pilot actions seem to lend themselves to scale-up more easily, but may compromise the level of participation intended by the original project design. Within participatory research, successful scale-up will require deciding whether an innovation is appropriate for the intended context, whether it can address complex problems like health equity, and whether reducing participatory elements for the sake of improved scalability is acceptable. Conclusion It is essential to develop novel theoretical concepts of scalability that account for the diversities identified within participatory projects observed in our study. The findings can guide future research on strategies to improve the effective implementation and scale-up or participatory physical activity innovations, ensuring that these remain adaptable and sustainable across various settings.